Hubungan Dukungan Sosial dengan Tingkat Kebahagiaan pada Mahasiswa Perantau Psikologi Universitas Negeri Padang - Adissah Putri Herdiati; Khairiah Rawita; Rahid Azizul Hakim; Ramilah Suta; Wirza Feny Rahayu (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This research aims to find out whether there is a relationship between social support and happiness in migrant students at the Faculty of Psychology, Padang State University. This research uses quantitative methods with a correlational design. A total of 100 migrant students were randomly selected as samples. Data was collected using a questionnaire about social support and happiness which has been proven to be valid and reliable. The results of the analysis show that social support has a significant positive relationship with happiness, with a correlation value of r = 0.575 (p < 0.05). This means, the more social support students receive, the happier they are. This research confirms that social support, whether from family, friends, or the campus community, really helps migrant students face the challenges of life in new environment. Therefore, it is important to strengthen social support networks to increase the happiness of migrant students.